2007
DOI: 10.1186/1742-6405-4-25
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial vaginosis and human immunodeficiency virus infection

Abstract: Epidemiologic studies indicate that bacterial vaginosis (BV), a common alteration of lower genital tract flora in women, is associated with increased susceptibility to HIV infection. Other recent studies show that HIV is detected more frequently and at higher levels in the lower genital tract of HIV-seropositive women with BV. In vitro studies show that genital tract secretions from women with BV or flora associated with BV induce HIV expression in infected cells. The increased HIV expression appears to be due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 45 publications
0
59
0
Order By: Relevance
“…In BV, however, increased numbers of bacteria, such as Gardnerella vaginalis, Bacteroides spp, Mobiluncus spp, Prevotella spp and Mycoplasma hominis, replace them [1]. The reported prevalence of BV in pregnant women ranges from 14% to 21% in Western countries [2][3][4], and a prevalence rate of 40.8% was reported in a non-pregnant population in southern Nigeria [5]. A case study done in Ghana showed a low prevalence of 1.4% among antenatal women [4].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In BV, however, increased numbers of bacteria, such as Gardnerella vaginalis, Bacteroides spp, Mobiluncus spp, Prevotella spp and Mycoplasma hominis, replace them [1]. The reported prevalence of BV in pregnant women ranges from 14% to 21% in Western countries [2][3][4], and a prevalence rate of 40.8% was reported in a non-pregnant population in southern Nigeria [5]. A case study done in Ghana showed a low prevalence of 1.4% among antenatal women [4].…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of HIV in genital secretions indicates that HIV infectiousness and susceptibility may be greater in the presence of concurrent reproductive tract infections [8,9]. Also significant is the sharp decline in the concentration of HIV in genital secretions when the infection is treated [1,2,8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Females with bacterial vaginosis are at higher risk of preterm delivery, pelvic inflammatory disease and infertility (5-7). Several epidemiological studies have shown that bacterial vaginosis is related to the increase in susceptibility to infection of human immunodeficiency virus (8).…”
Section: Introductionmentioning
confidence: 99%